2018
DOI: 10.1007/s00520-018-4175-4
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of HMB/Arg/Gln against oral mucositis induced by chemoradiotherapy for patients with head and neck cancer

Abstract: UMIN000016453.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 24 publications
0
39
0
Order By: Relevance
“…Matsuhashi et al reported that such supplementation was apparently effective in the treatment of anti-epidermal growth factor receptor antibody-associated skin disorder (22). Yokota et al conducted a phase II study that showed the efficacy of HMB, L-arginine and L-glutamine supplementation for chemoradiotherapyinduced oral mucositis in patients with head and neck cancer (23). These findings would suggest a preventive effect of HMB, L-arginine and L-glutamine against HFSR in patients with HCC treated with sorafenib.…”
Section: Discussionmentioning
confidence: 99%
“…Matsuhashi et al reported that such supplementation was apparently effective in the treatment of anti-epidermal growth factor receptor antibody-associated skin disorder (22). Yokota et al conducted a phase II study that showed the efficacy of HMB, L-arginine and L-glutamine supplementation for chemoradiotherapyinduced oral mucositis in patients with head and neck cancer (23). These findings would suggest a preventive effect of HMB, L-arginine and L-glutamine against HFSR in patients with HCC treated with sorafenib.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical and preclinical data suggested that arginine (Arg) and ornithine (Orn) supplementation are the most effective in increasing collagen deposition. However, whether this was accomplished by conversion to proline has not been confirmed [25,33]. It is known that glutamine plays a key role in protein metabolism.…”
Section: Sources Of Proline For Collagen Biosynthesismentioning
confidence: 99%
“…Of the 915 articles, 893 were potentially eligible for inclusion and 802 were then excluded based on title and abstract. After full texts were obtained and eligibility criteria applied to the remaining 91 articles, 23 articles 23,24,28‐49 were included in the review (total unique study participants n = 7605; Table 1). These included five systematic reviews with meta‐analyses 23,41,43‐45 ; six systematic reviews, 24,34,35,38,39,46 two randomised controlled trials (RCTs) 30,33 ; one non‐randomised controlled trial 48 ; four prospective cohort studies 32,37,42,47 ; two retrospective cohort studies 29,31 and three case series 28,36,40 …”
Section: Resultsmentioning
confidence: 99%
“…Articles investigating more than one intervention were eligible to fall into multiple intervention review areas. These included: oral cryotherapy (five studies; n = 1777) 29,30,39,41,44 ; elemental oral nutrition supplements (five studies; n = 186) 31,32,36,37,42 ; beta‐hydroxy‐beta‐methylbutyrate‐, arginine‐ and glutamine‐enriched (HMB/Arg/Gln) powdered supplement (two studies; n = 64) 47,48 ; immune‐modulating oral nutrition supplements (one study; n = 40) 28 ; fat‐soluble vitamins (two studies; n = 103) 23,46 ; glutamine supplementation (five studies; n = 2050) 24,33,38,40,46 ; zinc supplementation (three studies; n = 1009) 34,43,46 ; miscellaneous mineral supplements (two studies; n = 1188) 34,46 and honey (three studies; n = 1292) 35,45,46 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation